2018
DOI: 10.1186/s12891-018-2266-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between paraspinal muscle morphology and neurocompressive conditions of the lumbar spine: a systematic review with meta-analysis

Abstract: BackgroundIndividual study results have demonstrated unclear relationships between neurocompressive disorders and paraspinal muscle morphology. This systematic review aimed to synthesize current evidence regarding the relationship lumbar neurocompressive disorders may have with lumbar paraspinal muscle morphology.MethodsSearches were conducted in seven databases from inception through October 2017. Observational studies with control or comparison groups comparing herniations, facet degeneration, or canal steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 65 publications
7
51
0
1
Order By: Relevance
“…All muscle and fat within these boundaries were included. These measurement parameters accord with recent recommendations for assessing paraspinal muscle morphology [14,31]. A detailed description of the outlining parameters applied, including methods for addressing variations from the "normal" boundary appearances, can be found in Additional le 1.…”
Section: Muscle Morphology Measurement Proceduressupporting
confidence: 60%
“…All muscle and fat within these boundaries were included. These measurement parameters accord with recent recommendations for assessing paraspinal muscle morphology [14,31]. A detailed description of the outlining parameters applied, including methods for addressing variations from the "normal" boundary appearances, can be found in Additional le 1.…”
Section: Muscle Morphology Measurement Proceduressupporting
confidence: 60%
“…A meta-analysis of 28 studies that evaluated the impact of lumbar disc herniation, facet degeneration, or canal stenosis on lumbar paraspinal muscle morphology, concluded that disc herniation and severe facet degeneration were associated with altered paraspinal muscle morphology at, or below, the pathology level. 31 However, the authors highlighted the different measurement techniques in these studies and the need for a consensus on measurement methods, and recommend measurement techniques for standardization. 31 The authors also noted that normalization of brightness for pixel intensity assessment is a matter of importance to reduce variability between equipment and facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Further, due to the morphological complexity of thoracolumbar muscles where intramuscular variations like fibre length exist within and between vertebral levels and regions, we recommend that intra-muscular regions be considered separately and at multiple vertebral levels to identify age-related modifications to function. New evidence is pointing the importance of specific intervertebral level to muscle composition in neurocompressive (and degenerative) conditions of the lumbar spine,[ 54 ] which age strongly influences.…”
Section: Discussionmentioning
confidence: 99%